1105. A Matched-Group Comparison of Interventions for COVID-19 During the First and Second Waves of the COVID-19 Pandemic in a County Hospital in Chicago. (15th December 2022) - Hernandez Acosta, Ruben A; Corpuz, Carlos; Gonakoti, Sriram; Patel, Palak; Chang, Hillary; Akaho, Elikplim; Skaathun, Britt; Hoffman, Michael; Rezai, Katayoun
Abstract: Background: The COVID-19 pandemic continually challenges the scientific community to develop and evaluate viable treatments. In May 2020, remdesivir became the first medication to receive emergency use authorization for the treatment of COVID-19, while dexamethasone became standard of care for patients requiring supplementary oxygen in late 2020. Methods: This was a retrospective observational study of hospitalized adult patients with confirmed coronavirus disease 2019 (COVID-19) admitted in the first wave (3/2020-7/2020) and second wave (10/2020-1/2021) at Cook County Hospital. Variables on demographic, clinical data and outcomes were extracted from the EMR. The measured intervention was use of dexamethasone with remdesivir during the second wave; patients were matched by age and diabetic status to patients in the first wave who had received only remdesivir. The primary outcome was mortality; secondary outcomes were ICU admission and intubation. Conditional logistic regression was used to examine associations between use of dexamethasone and each outcome, controlling for glucose levels, use of remdesivir and severity of disease. Results: 621 patients were admitted in the first wave (3/2020-7/2020) versus 355 in the second wave (12/2020-1/2021). Median age was 55 years and 56 years, respectively. Most patients were Hispanic and Black. In the first wave, 296 patients (48%) were admitted with severe COVID-19 (defined as oxygen saturation on room air at or below 94%) versus 163 patients (46%) in the second wave. Logistic regression showed no association between use of dexamethasone and ICU admission, mortality or intubation. Use of remdesivir showed no association with any of the outcomes. Glucose and severe/critical disease were strongly associated with ICU admission (p=0.01 and p=0.003) and mortality (p=0.06 for both). Conclusion: Despite promising medications, in this study the mortality and disease severity of COVID-19 was very similar to that seen in the first wave. This could be due to patients presenting with more advanced disease and undiagnosed or poorly-controlled comorbidities that may offset the potential benefit of these treatments. Enhancing access to care and decreasing health inequalities may be more worthwhile than finding a "miracle drug". Disclosures: All Authors : No reported disclosures.